Adjuncts to the Management of Graft Aorto-Enteric Erosion and Fistula with in situ Reconstruction. (November 2021) - Mauriac, Paul; Francois, Marc-Olivier; Marichez, Arthur; Dubuisson, Vincent; Puges, Mathilde; Stenson, Katherine; Ducasse, Eric; Caradu, Caroline; Berard, Xavier
Abstract : Objective: The objective of this retrospective single centre study was to determine whether different enteric reconstruction methods and adjuncts confer a benefit after in situ reconstructions (ISRs) of graft aorto-enteric erosion (AEnE) and fistula (AEnF). Methods: Primary endpoints were in hospital mortality and AEnE/F recurrence. Survival was estimated using the Kaplan–Meier method and explanatory factors were searched for using uni- ± multivariable Cox regression analysis. In 2013, a multidisciplinary team meeting was convened and since then the primary operator has always been a senior surgeon. Results: Sixty-six patients were treated for AEnE ( n = 38) and AEnF ( n = 28, 42%) from 2004 to 2020. All patients with AEnF presented with gastrointestinal bleeding ( vs. 0 for AEnE; p < .001). Signs of infection were seen in 50 patients (76% [37 for AEnE vs. 13 for AEnF]; p < .001). Referrals for endograft infection increased over time ( n = 15, 23%; one before 2013 vs. 14 after; p = .002). Most patients underwent complete graft excision ( n = 52, 79%) with increasing suprarenal cross clamping ( n = 21, 32%; four before 2013 vs. 17 after; p = .015). Complex visceral reconstructions decreased over time ( n = 31, 47%; 17 before 2013 vs. 14 after; p = .055), while "open abdomens" (OAs) increased (one before 2013 vs. 22 after; p < .001), reducing operating time ( p = .012). In hospital mortality reached 42% ( n = 28). Estimated survival reached 47.6% (95% confidence interval [CI] 35.0 – 59.1) at one year and 45.6% (95% CI 33.0 – 57.3) at three years and was higher for AEnE than for AEnF (log rank p = .029). AEnE/F recurrence was noted in 12 patients (18%). Older age predicted in hospital mortality in multivariable analysis ( p = .034). AEnE/F recurrence decreased with the presence of a primary senior surgeon ( vs. junior; p = .003) and OA (1 [4.4%] vs. 11 [26%] for primary fascial closure; p = .045) in univariable analysis. Conclusion: Mortality and recurrence rates remain high after ISR of AEnE/F. Older age predicted in hospital mortality. Primary closure of enteric defects ≤ 2 cm in diameter reduced operating time without increasing the recurrence of AEnF.